QUALITY OF WORK-LIFE BALANCE DALAM KUALITAS KEHIDUPAN KERJA TERHADAP KEPUASAN KERJA, KOMITMEN ORGANISASI, DAN MOTIVASI KERJA DI UNIVERSITAS MUHAMMADIYAH BANJARMASIN - Ngalimun Ngalimun; Imam Mujahid; Imam Makruf (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2022)
This study aims to examine the effect of work-life balance on the quality of work life on job satisfaction, organizational commitment and work motivation. The results showed that work-life balance had a significant effect on job satisfaction, but work-life balance did not have a significant effect on organizational commitment and work motivation. This research is a descriptive study – single cross sectional. The type of data used in this study is primary data in the form of a questionnaire. The population of this study is an educator at the University of Muhammadiyah Banjarmasin. The number of samples required in this study were 25 respondents from a total population of 100 people. The main problem in this research is that educational institutions or companies must be able to provide a proper place for their employees considering that their contribution is very important in carrying out activities so that an institution or company can be sustainable.